2019
DOI: 10.1016/j.joule.2019.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Ambient Fabrication of High-Performance CsPbI2Br Solar Cells

Abstract: All-inorganic halide perovskites hold promise for emerging thin-film photovoltaics due to their excellent thermal stability. Unfortunately, it has been challenging to achieve high-quality thin films over large areas using scalable methods under realistic ambient conditions. Here, we provide important lessons on controlling the solidification and crystallization of CsPbI2Br perovskite inks during ambient scalable fabrication, with results of superior thin-film quality and device performance compared to lab-scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
131
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(132 citation statements)
references
References 67 publications
1
131
0
Order By: Relevance
“…[34,35,41,42] Recently, a few studies have been reported for the film formation during solution processing of mixed-cation mixed halide perovskites. [43][44][45] For instance, Qin et al investigated film formation during spin coating for Cs x (FA 0.83 MA 0.17 ) 1−x Pb(I 0.83 Br 0.17 ) 3 and revealed the role of Cs in suppressing the formation of hexagonal polytypes (4H, 6H). [43] Szostak et al investigated the impact of precursor solvents, humidity, and dropping antisolvent on the film formation for Cs 0.17 FA 0.83 Pb(I 0.83 Br 0.17 ) 3 and MA 0.17 FA 0.83 Pb(Br 0.17 I 0.83 ) 3 during spin coating.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[34,35,41,42] Recently, a few studies have been reported for the film formation during solution processing of mixed-cation mixed halide perovskites. [43][44][45] For instance, Qin et al investigated film formation during spin coating for Cs x (FA 0.83 MA 0.17 ) 1−x Pb(I 0.83 Br 0.17 ) 3 and revealed the role of Cs in suppressing the formation of hexagonal polytypes (4H, 6H). [43] Szostak et al investigated the impact of precursor solvents, humidity, and dropping antisolvent on the film formation for Cs 0.17 FA 0.83 Pb(I 0.83 Br 0.17 ) 3 and MA 0.17 FA 0.83 Pb(Br 0.17 I 0.83 ) 3 during spin coating.…”
Section: Introductionmentioning
confidence: 99%
“…[44] Fan et al probed the crystallization of all inorganic perovskites during blade coating and revealed the effect of blade-coating conditions on perovskite formation. [45] However, a comparison of the mechanism of different processing treatments during spin coating versus blade coating for mixed cation perovskites is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, mixed‐halide CsPbI (3 − y ) Br y perovskites were explored to balance the trade‐off between bandgap and stability. In particular, CsPbI 2 Br perovskite has been considered as a potential candidate for inorganic PSC due to its reasonable bandgap (≈1.9 eV) and much improved ambient stability . However, it is still structurally unstable and can easily transform into nonperovskite orthorhombic phase under prolonged exposure to high humidity .…”
Section: Introductionmentioning
confidence: 99%
“…As one of the effective approaches to utilize solar energy converting energy, photovoltaics have received extensive attention. Achieving high-efficiency, large-area manufacture, and excellent environmental stability are the goals (Liu et al, 2015;Niu et al, 2018;Fan et al, 2019;Xu et al, 2019a,b;Zhu et al, 2019;Zhang et al, 2020). Especially, organic photovoltaic devices (OPVs) using solution-processible donor-acceptor bulk heterojunction (BHJ) as photon-harvesting active layer are attractive for next-generation flexible photovoltaic modules (Li et al, , 2018Lin et al, 2012;Heeger, 2014;Dong et al, 2019).…”
Section: Introductionmentioning
confidence: 99%